Together or separate? Tracing classroom pedagogies of (un)belonging for newcomer migrant pupils in two Austrian schools - Wagner, Josefine; Szelei, Nikolett; Eloff, Irma; Acquah, Emmanuel (Frontiers in Education, 2024)
Even though receiving newcomer pupils in schools is not a new phenomenon, many education systems grapple with finding adequate schooling arrangements that foster belonging and inclusion. Over the years, policy-makers and school practitioners seem to echo recurring dilemmas in terms of what language support models may promote optimal inclusion, and whether and how to support the language of schooling while also building on students’ cultural and linguistic repertoires. In this article, we present classroom observations from two Austrian primary schools that implemented German language support in two distinct ways. School 1 implemented pull-out classes, whereas School 2 used a model of individualized learning for all students in the mainstream classroom. Utilizing the cultural-linguistic aspects of ‘belonging’ in pedagogical enactments, we analyze how teachers’ instructional strategies to organize curricular learning for newly arrived migrant pupils set conditions for pedagogies of (un)belonging in the classroom. Findings show that pedagogies of (un)belonging seemed to be formed via chains of patterned interactions, activities and utterances based on three key logics: marking students’ ‘fitness’ to the mainstream classroom, creating cultural (in)visibility, and as creating language hierarchies. While the two classroom practices remarkably differed in how they enabled German language learning and fitting to mainstream pedagogical norms, both seemed to uphold monolingualism and monoculturalism. Recommendations are given in order to expand narrow notions of belonging in educational policy and practice.